RANCANG BANGUN SISTEM PENYIRAMAN TAMAN HOTEL OTOMATIS BERBASIS INTERNET OF THINGS (IOT) MENGGUNAKAN ESP8266 - Ryan Handika, I Made; Diafari Djuni Hartawan, I Gst A. Komang; Ary Esta Dewi Wirastuti, i Made (Jurnal SPEKTRUM, 2022)
COVID-19 is a virus that attacks the respiratory system, has a negative impact on health. The impact of the pandemic is the reduced number of tourists visiting the island of Bali, making sources of income very limited. This directly has a detrimental impact on hotel managers in Bali. With the policy of reducing the number of employees, it is clearly detrimental to all parties and we can see that several hotel facilities have been damaged, one of which is in the garden. In this final project, a garden watering system based on the Internet of Things was designed using ESP8266. This system works according to a programmed watering schedule, rain sensor readings, and soil moisture sensors. The tool will water the garden when the time conditions are met, the rain sensor detects the absence of rain around the park and also when the relay is active, it flows voltage to the solenoid valve to open the water flow to the Sprinkler. Then the watering data will be sent to the Thingspeak cloud which will also be accessible by applications on smartphones. Monitoring information will be displayed on the LCD and also the application on the smartphone. An IoT-based automatic hotel garden watering system prototype using ESP8266 is able to run according to design.